2015
DOI: 10.1042/bj20150049
|View full text |Cite
|
Sign up to set email alerts
|

Retrocyclins neutralize bacterial toxins by potentiating their unfolding

Abstract: Defensins are a class of immune peptides with a broad range of activities against bacterial, fungal and viral pathogens. Besides exerting direct anti-microbial activity via dis-organization of bacterial membranes, defensins are also able to neutralize various unrelated bacterial toxins. Recently, we have demonstrated that in the case of human α- and β-defensins, this later ability is achieved through exploiting toxins’ marginal thermodynamic stability, i.e. defensins act as molecular anti-chaperones unfolding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Thus, it has been demonstrated that a conserved Trp-26 residue is essential for HNP-1 activity as a contributor to hydrophobicity for interaction with target molecules and for formation of dimers15. However, retrocyclins, which are similarly active against viral (current study) and bacterial effectors12, do not have tryptophans, suggesting that the role of this residues is fulfilled by other structural elements. In the absence of a detailed and quantifiable model, we can provide only speculative explanation to the observed differences in activities of the peptides.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, it has been demonstrated that a conserved Trp-26 residue is essential for HNP-1 activity as a contributor to hydrophobicity for interaction with target molecules and for formation of dimers15. However, retrocyclins, which are similarly active against viral (current study) and bacterial effectors12, do not have tryptophans, suggesting that the role of this residues is fulfilled by other structural elements. In the absence of a detailed and quantifiable model, we can provide only speculative explanation to the observed differences in activities of the peptides.…”
Section: Discussionmentioning
confidence: 80%
“…41 Precipitation of bacterial toxins in the presence of defensins has been also described as a mechanism the inactivation of some bacterial toxins by these types of peptides. 42 In our study, however, we did not see any evidence of protein precipitation under the conditions used in our assays.…”
Section: Discussionmentioning
confidence: 99%
“…The toxin is comprised of several well-defined components: i) a variable number (from one to five) of effector domains with distinct toxicities found in different combinations; ii) a cysteine protease domain (CPD) always positioned C-terminally to the effector domains and responsible for domain liberation upon delivery into a host cell (Prochazkova et al, 2009; Shen et al, 2009); and iii) the N- and C-terminal glycine-rich Ca 2+ -binding repeats that serve for membrane integration and translocation across the membrane (Kim et al, 2015). The specific enzymatic activity of one of the MARTX effector domains, actin cross-linking domain (ACD; (Heisler et al, 2015; Kudryashova et al, 2016a)) produced by V. cholerae and A. hydrophila , was tested in vitro and found to be potently inhibited by α- (HNP1, HD5; (Kudryashova et al, 2014b)) and θ-defensins (RC1 and RC101; (Kudryashova et al, 2015)). Cytotoxicity of both ACD and Rho inhibitory effector domain (RID; (Ahrens et al, 2013)) was prevented by HNP1 in cell culture experiments (Kudryashova et al, 2014b).…”
Section: Defensin-susceptible Bacterial Toxins/effector Proteinsmentioning
confidence: 99%
“…Just over a decade ago, a group of AMPs called defensins was reported to efficiently neutralize anthrax toxin both in vitro and in an animal model (Kim et al, 2005). In the following years, it became increasingly clear that a small set of defensins are universal effector molecules capable of neutralizing numerous toxins, many of which are unrelated to each other (Giesemann et al, 2008; Hooven et al, 2012; Kim et al, 2006; Kudryashova et al, 2014b; Kudryashova et al, 2015; Lehrer et al, 2009; Wang et al, 2006; Welkos et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation